What Determines Internal Control Weakness? An Empirical Analysis of State-owned Enterprises Audited by State Audit Agency - Ronny Prabowo; Hosanna Christy; Benedicta Dyas Ayu Nitasari (Jurnal Akuntansi dan Bisnis, 2008)
A material weakness in internal control is defined as a significant deficiency, or combination of significant deficiencies, that result in more than a remote likelihood that a material misstatement of the annual or interim financial statement will not be prevented or detected. Section 404 of the Sarbanes-Oxley Act (Management Assessment of Internal Controls) stipulates that management of publicly listed firms has to evaluate the effectiveness of their internal controls over financial reporting and disclose the identified material weakness. Numerous articles aim to find empirical evidence of factors influencing weakness of internal control. In Indonesia, publicly listed firms are yet obliged to disclose their material weakness of internal control. However, BPK (as the state audit agency) report the material weakness of internal control over entities’ financial reporting in their audit report of state-owned enterprises (SOE or BUMN). The report enables us to empirically analyze influencing factors of internal control weakness over BUMN financial reporting. There are four independent variables to be hypothesized to influence internal control weakness (WEAK): profitability (PROFIT), firm size (SIZE), growth rate (GROWTH), and the presence of complex transaction (COMPTRANS). Additionally, we also employ one control variable (FORM or legal form of SOE: Persero or non-Persero). Empirical results show that without control variables, only SIZE is significantly associated with WEAK (for univariate and multivariate analysis). However, the direction of effect of SIZE on WEAK (positive) is contradictory with the hypothesized direction (negative). After including control variables, the power of regression equation is slightly increasing. However, still only SIZE significantly affect WEAK with contradictory direction.